Antibiotic prophylaxis in surgery for closed fracture of the hand - Lidauer, Kristian; Helenius, Ilkka; Pääkkönen, Markus (Elsevier Masson s.r.l., 2025)
Purpose: Preoperative antibiotic prophylaxis is associated to internal fixation for closed phalangeal and metacarpal fracture, but its effectiveness is not known.
Methods: In a consecutive series of 119 adult patients undergoing Kirschner-wire fixation for phalangeal or metacarpal fracture, 56.3% (n = 67) received antibiotic prophylaxis and 43.7% (n = 52) did not.
Results: The rate of deep surgical site infection was 1.5% (n = 1) in the group with antibiotic prophylaxis and 1.9% (n = 1) in the group without. Minor skin irritation or infection of the pin tract occurred in 13.4% of cases (n = 9) in the group with antibiotic prophylaxis and 9.6% (n = 5) in the group without.
Conclusion: Our findings suggest that use of antibiotic prophylaxis could be reduced in the treatment of closed fractures of the hand treated with removable pins. Type of study/level of evidence: Therapeutic IV (retrospective review).